Manifesting Grammatical Meanings and Functions of Particle â€œLahâ€ in PÃ©gon Script (Javanese Translation) of SyiÊ»ir QiyÄmah - Hendrokumoro,; Ma'shumah, Nadia Khumairo; Irakusuma, Ratna Nur Fatimah (OKARA: Jurnal Bahasa dan Sastra, 2023)
Linguistics researchers and academics frequently overlook the presence of particles in sentence constructions. Nonetheless, language is never presented in a vacuum. Any-faceted phenomenon can be â€˜meansâ€™ in many different ways and can be explored from many different points of view. This study discussed the grammatical meanings and functions of the particle lah in SyiÊ»Ä«r or Singir. Qualitative data collected in this study were obtained from SyiÊ»Ä«r QiyÄmahâ€™s PÃ©gon script, consisting of recto (introduction) and chapters from 16 pages with the amount of 16 verses. Meanwhile, all the data were analyzed by combining philology and linguistics studies to comprehend and interpret language in written historical sources. The findings of this study indicate that the grammatical meanings of this particle lah were highly contested and varied due to the particle lah's different position in Javanese clause/ sentence construction. Given that the particle lah has no lexical meaning of its own, its meaning is inextricably linked to the context of the sentence in which it appears. Through meticulous investigation, this study discovered four grammatical meanings of particle lah in SyiÊ»Ä«r QiyÄmahâ€™s PÃ©gon script: (1) as the interjectors, (2) as taukid, (3) as conjunctures, and (4) as separators; as well as three functions of particle lah in SyiÊ»Ä«r QiyÄmahâ€™s PÃ©gon script: (1) to highlight the information that was considered important; (2) to connect one information with another; and (3) to emphasize the importance of elements in the information unit.